The effect of using the Karen model on the achievement of fifth grade literary students in rhetoric (Journal of the College of Basic Education, 2022)
The research aims to know the effect of using the Karen model on the literary achievement of fifth grade students in rhetoric. The researcher developed a null hypothesis, and selected a sample of fifth-grade literary students in the Suez Preparatory School for Boys affiliated to the General Directorate of Education of Baghdad/First Rusafa.The researcher rewarded the two groups, set behavioral goals, prepared model plans, and a post achievement test, which he applied to the research sample. The results were in favor of the experimental group, and the researcher made some recommendations and suggestions.